Determination of vitamin D levels in food samples and effect of calcium on regulation of vitamin D absorption - Osman, Nurul Nadiah (2018)
Many published findings showed that vitamin D status is low across wide ranges of populations and age groups. These concerns need to be considered in the context of developing countries where dietary supplements can be very expensive. Hence, it is necessary to determine vitamin D content available in Malaysia food products rather than merely depending on nutritional supplement which is beyond affordability for certain groups of people. The purpose of this research is to sample and analyse inexpensive foods considered to be major contributors of vitamin D that are readily available in the Malaysian market. The vitamin D compounds in 13 food samples were determined by extraction process using Ultra High Performance Liquid Chromatography (UHPLC). Among these 13 food samples the local oyster mushroom (Pleurotus ostreatus) contain 1143.6 IU of vitamin D was chosen to undergo further fractionation process, as oyster mushrooms are one of the few food sources where the precursor to vitamin D occurs naturally. Since calcium is a nutrient component that needed by Vitamin D in order to be absorp by human body. It is worth to study the regulation of calcium in vitamin D absorption by in vitro methods using Caco-2 cells, which believed to be more practical and inexpensive methods compared to in vivo methods. There were two types vitamin D that have been used in this study which are 1,25-dihydroxyvitamin D2 and 1,25- dihydroxyvitamin D3. In the calcium uptake study, 1,25-dihydroxyvitamin D3 were absorbed more efficiently compared to 1,25-dihydroxyvitamin D2 after the addition of calcium. Thus, it can be concluded that the presence of calcium would help to increase the absorption of vitamin D into the intestinal cell and 1,25-dihydroxyvitamin D3 was absorbed more readily compared to 1,25-dihydroxyvitamin D2.